Role of Mucosal and Reproductive Tract Microbiota in Postoperative Infectious Complications following Multisite Surgical Procedures in Women - Naeem Ullah Khan, Hameedullah Achakzai, Najma Khurshid, Abrar ul Hassan Pirzada, Alina Mehwish, S. Iftikhar Alam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mucosal and reproductive tract microbiota play a crucial role in maintaining immune balance and preventing infections. Alterations in the microbiota may play an important role in the risk of postoperative infections among women undergoing multisite surgeries. Objective: To evaluate the association between mucosal and reproductive tract microbiota composition and postoperative infectious complications in women undergoing multisite surgical interventions. Methods: This cross-sectional clinical study was conducted from June 2022 to May 2023 at Bolan Medical College and DHQ Teaching Hospital. A total of 120 female patients undergoing multisite surgical procedures were enrolled. Microbiota from vaginal, rectal, and skin sites were collected preoperatively and assessed through culture and 16S rRNA methods. Patients were followed for 30 days postoperatively to assess surgical site infections, pelvic infections, urinary tract infections, and systemic complications. Chi-square tests and logistic regression were used for statistical analysis, with a p-value of < 0.05 considered significant. Results: Postoperative infections were observed in 31.7% of patients. Infection rates were significantly higher in patients with microbiota dysbiosis (52.6%) compared to those with normal microbiota (14.3%) (p < 0.001). Multisite colonization was strongly associated with infection severity (58.1%). Dysbiosis was identified as an independent predictor of infection (OR = 3.45, 95% CI: 1.89–6.31). Elevated inflammatory markers, including CRP and IL-6, were significantly associated with microbial imbalance. Conclusion: Microbiota dysbiosis of the mucosal and reproductive tracts is a strong predictor of postoperative infection in women with multisite surgery. Testing the microbiota preoperatively may be used to stratify the risk and develop preventive strategies. Keywords: microbiota, dysbiosis, postoperative infection, surgical site infection, vaginal microbiome, inflammation.